UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN AGAMA MELALUI METODE BILLBOARD RANKING PADA SISWA KELAS XII.IPS 3 SMA N 1 RANAH BATAHAN - Adisman, Adisman (Jurnal Manajemen Pendidikan, 2017)
Based on the results of student learning Class XII.IPS 3 SMA N 1 Ranah Batahan in the subjects of Religion found that the results of student learning in Religious subjects is still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about Efforts to Improve student learning outcomes in subjects Religion sub Reading Al-Qur'an of Jonah and Surat al-Baqarah, Explaining the meaning of developing science and technology as contained in the Quran: Surat Yunus and Al- Baqarah through Billboard Ranking Method in Class XII.IPS 3 SMA N 1 Ranah Batahan Pasaman Barat Regency. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. Research subjects consist of 29 students of Class XII.IPS 3 SMA N 1 Ranah Batahan. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion have been put forward, it can be concluded that Billboard Ranking Method can improve student learning outcomes in subjects Religion sub Reading the Qur'an letter of Yunus and Surat al-Baqarah, Explaining the meaning of development of science and technology as contained in the Quran : Surat Yunus and Al-Baqarah in SMA N 1 Ranah Batahan. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 57.41 (Enough) increased to 84.17 (Good) with an increase of 26.76%.